2010
DOI: 10.1007/s11239-010-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ischemic stroke and transient ischemic attack in patients under age 50

Abstract: To analyze risk factors for ischemic stroke and transient ischemic attack (TIA) in young adults under the age of 50. To make recommendations for additional research and practical consequences. From 97 patients with ischemic stroke or TIA under the age of 50, classical cardiovascular risk factors, coagulation disorders, history of migraine, use of oral contraceptives, cardiac abnormalities on ECG and echocardiography, and the results of duplex ultrasound were retrospectively analyzed. Literature was reviewed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
2
24
3
1
Order By: Relevance
“…A very similar profile of classic vascular risk factors in young ischemic stroke patients has also been reported elsewhere, however, differing in the order of frequency [3][4][5][6][7][15][16][17][18][19]. These results show that conventional vascular risk factors are significant risk factors for ischemic stroke not only in the >55 age group, but also in younger population.…”
Section: Discussionsupporting
confidence: 87%
“…A very similar profile of classic vascular risk factors in young ischemic stroke patients has also been reported elsewhere, however, differing in the order of frequency [3][4][5][6][7][15][16][17][18][19]. These results show that conventional vascular risk factors are significant risk factors for ischemic stroke not only in the >55 age group, but also in younger population.…”
Section: Discussionsupporting
confidence: 87%
“…Hypertension and hyperlipidemia were also quite common in these studies (22-56 and 17-59%, respectively), in approximately the same levels as in our study (31.4 and 27.6%, respectively). Diabetes was found in 6.7% of our patients, i.e., with a similar frequency as in other comparable studies (5-17%) [5,9,15,18,19]. Overall, 58.7% patients had one or more atherosclerotic risk factors (not counting smoking), which is close to what [11].…”
Section: Risk Factorssupporting
confidence: 89%
“…In our population, the most common risk factor was smoking (55.2%). Other studies on young stroke patients have also found a high percentage of smokers; however, not as high as in our study (37-44%), with the exception of the study performed by Spengos et al, who found almost 60% of smokers in their population of Greek stroke patients [5,9,15,18,19]. Hypertension and hyperlipidemia were also quite common in these studies (22-56 and 17-59%, respectively), in approximately the same levels as in our study (31.4 and 27.6%, respectively).…”
Section: Risk Factorscontrasting
confidence: 87%
“…Some studies reported a higher prevalence of uncommon aetiologies such as cervical arterial dissection (CAD) or stroke related to pregnancy or migraine [2][3][4][5] , whereas more recent studies suggested surprisingly similar risk factor profiles in young and old stroke patients [6][7][8] . One study with patients under 50 years showed a high percentage (47.9%) of previous cardio-or cerebrovascular events, which is in line with the latter findings [7] .…”
mentioning
confidence: 99%